Competing destinations and intervening opportunities interaction models of inter-city telecommunication flows - Jean-Michel Guldmann (European Regional Science Association (ERSA), 1998)
This research makes use of a large sample (600,000) of individual telephone calls between local exchanges (cities, villages) within a U.S. region. Callers and callees are identified by their 4-digit SIC (Standard Industrial Classification) code. The intersectoral and interlocational flows (number of messages and conversation minutes) are aggregated into major economic sectors (Agriculture, Manufacturing, Retail Trade ...., and Households), and are analyzed by estimating, in a simultaneous equation framework, spatial interaction models that account for (1) the role of the spatial structure, which reflects the competition and agglomeration effects that take place among the flow destinations, and (2) the role of the reverse flows, which reflect the process of information creation necessary to complete intersectoral economic transactions. A particular focus is set on Fotheringham's competing destinations model and Stoufer's intervening opportunities model, while accounting for the effects of place hierarchy. A theoretical framework is presented, to guide the interpretation of the empirical results and their policy implications regarding the impacts of telecommunications deregulation, transportation and telecommunications interactions, and the role of information technologies in fostering the development of rural and peripheral areas.
Keywords: 330